Transient, small-scale field-aligned currents in the plasma sheet boundary layer during storm time substorms - Nakamura, R (Geophysical research letters, 2016)
We report on field-aligned current observations by the four Magnetospheric Multiscale (MMS) spacecraft near the plasma sheet boundary layer (PSBL) during two major substorms on 23 June 2015. Small-scale field-aligned currents were found embedded in fluctuating PSBL flux tubes near the separatrix region. We resolve, for the first time, short-lived earthward (downward) intense field-aligned current sheets with thicknesses of a few tens of kilometers, which are well below the ion scale, on flux tubes moving equatorward/earthward during outward plasma sheet expansion. They coincide with upward field-aligned electron beams with energies of a few hundred eV. These electrons are most likely due to acceleration associated with a reconnection jet or high-energy ion beam-produced disturbances. The observations highlight coupling of multiscale processes in PSBL as a consequence of magnetotail reconnection